The Role of Knowledge Sharing, Job Stress, Mutations and Motivation in Improving Employee Performance - Supomo Supomo (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Organizations need to measure employee performance to determine the level of individual and organizational achievement, as well as a basis for career development, performance improvement, giving rewards and sanctions, and salary payments. Motivation is an important factor in encouraging employees to achieve organizational goals. However, motivating employees can be a challenge because each individual's preferences and motivational factors are different. Good mental health, where individuals are able to deal with stress and work productively, also play a role in performance. Employee transfers, which are based on leadership commitment and statutory regulations, can influence performance by placing employees in positions that are in accordance with their competencies. Knowledge sharing among employees, influenced by organizational culture and leadership support, can improve performance by facilitating access to information and experience. This article examines the influence of knowledge sharing, work stress, transfers, and motivation on employee performance.